Impact Of Work Life Balance On The Well-Being Of Pharmacist In Various Pharmaceutical Sectors - Estrella, J.P.; Khojasteh, A.; Suarez, M.A.C.; Jazul, Regina A. (STIKES Telogorejo Semarang, 2023)
Work-life balance (WLB) describes the ideal of splitting one's time and energy between work and other important aspects of their life. This study would benefit individuals and organizations to have a deeper understanding of the importance of a healthy balance between work and family demands and their effects on people’s wellbeing and organization’s performance. Quantitative research method was used, and respondents were selected through convenient sampling technique. The survey questionnaire with a Cronbach’s alpha of 0.87 was distributed to 150 respondents but only 138 were returned giving an overall returning rate of 92%. From the gathered data it was found that “flexibility in time” as the most available work-life balance benefits, while “socializing and leisure activities during weekend in order to maintain family relationship” were the problem frequently experienced. However, “respondents’ time needed at home” is the most conflict that interferes at work while, “work related duties” sometimes create a conflict with family activities. In conclusion, Work-life balance does not have impact on Family Satisfaction (r=0.11953) and Work Satisfaction (0.08541) but has minimal impact with Psychological Health (0.28).